Biophilic Architecture: A Sustainable Healing Strategy in Rehabilitation Centers in the Niger Delta Region of Nigeria - Dennis Ejike Amadi; Chima Ichendu (Innovation in Science and Technology, 2024)
This research analyzes the potential of Biophilic design as a sustainable healing technique in rehabilitation centers situated in the Niger Delta region of Nigeria. Drawing from the rich biodiversity and cultural past of the region, Biophilic design concepts are investigated as a technique to boost the physical and mental well-being of patients undergoing rehabilitation. By integrating natural components and patterns into the constructed environment, rehabilitation institutions can provide therapeutic places favorable to healing and recovery. In the context of rehabilitation institutions, adopting Biophilic design concepts can provide several benefits to patients, including stress reduction, enhanced mood, and speedier recovery. This paper presents strategies for applying Biophilic design in the Niger Delta’s rehabilitation centers and examines the socio-environmental benefits of such an approach.